2014
DOI: 10.1159/000365745
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Proteins Removed with High-Flux Membranes on High-Volume Hemodiafiltration Detected with a MultiDimensional LC-MS/MS Strategy

Abstract: Background: Aim of this prospective crossover study was to identify the nature of the middle-molecular weight solutes removed during high-volume post-dilution HDF. Methods: The efficiency in removing small molecules, protein-bound and middle-molecular proteins was evaluated in 16 chronic dialysis patients on post-dilution HDF with two high-flux dialyzer membranes (Amembris and Polyamix). Multidimensional Protein Identification Technology (MudPIT) was employed to identify middle-molecular weight solutes in spen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…HDF enhances their convective removal and is superior to HD in eliminating several small and larger uremic toxins [49, 50]. Of note, a complex pattern of >250 proteins is removed by HDF [51]. It is conceivable that some of these toxins may interact with the RBC glycocalyx and that their inferior removal may affect ESS.…”
Section: Discussionmentioning
confidence: 99%
“…HDF enhances their convective removal and is superior to HD in eliminating several small and larger uremic toxins [49, 50]. Of note, a complex pattern of >250 proteins is removed by HDF [51]. It is conceivable that some of these toxins may interact with the RBC glycocalyx and that their inferior removal may affect ESS.…”
Section: Discussionmentioning
confidence: 99%
“…Pedrini et al [ 63 ] employed Multidimensional Protein identification Technology to characterize in a prospective crossover study the removal of middle-molecular weight solutes during high-volume post-dilution hemodiafiltration (a mixed diffusive/convective dialytic technique) with two high-flux dialyzer membranes (Amembris and Polyamix). A total of 277 proteins were identified by the proteomic approach in the dialysate fluids, removal capability being higher with the Amembris membrane (B. Braun Avitum, Melsungen, Germany).…”
Section: Proteomic and Extracorporeal Blood Purificationmentioning
confidence: 99%
“…A total of 277 proteins were identified by the proteomic approach in the dialysate fluids, removal capability being higher with the Amembris membrane (B. Braun Avitum, Melsungen, Germany). This is another effort to steer research toward a better knowledge of uremic toxins and the balance between intended and unintended removal of undesired and beneficial proteins [ 63 ]. In a proteomic investigation on extracorporeal blood purification techniques, Monari et al [ 64 ] showed that HFR (HemoFiltration with endogenous on-line Reinfusion), an integrated dialysis technique that combines convection, diffusion, and adsorption, is better than standard HD at removing uremic toxins, especially medium-high MW molecules.…”
Section: Proteomic and Extracorporeal Blood Purificationmentioning
confidence: 99%
“…An important effort to identify and characterize uremic toxins, and to steer research toward a better knowledge of the balance between intended and unintended removal of undesired and beneficial proteins, was carried out by Pedrini et al using the multidimensional protein identification technology (MudPIT). 24 Two high-flux membranes (Amembris and Polyamix, a polyamide membrane) were used and compared in a randomized cross-over study carried out in 16 patients being dialyzed with high-volume post-dilution HDF. Both membranes displayed high efficiency in removing solutes of different MW in spent dialysate, with Amembris membrane showing higher capability.…”
Section: Introductionmentioning
confidence: 99%
“…Though the protein removal pattern was similar, the total and protein-specific peptide spectral count of most proteins was higher when using Amembris membrane. 24 The most abundant proteins identified by MudPIT technology in dialysate included not only the compounds of which the metabolic role and effects of accumulation in the uremic plasma are known, 1 such as complement factor D, β2-microglobulin, retinol-binding protein 4, and myoglobin, but also proteins with effects which are less fully described, such as alpha-1 microglobulin/bikunin precursor and prostaglandin D2 synthase. However, vital compounds such as vitamin D-binding protein were also detected in both datasets from the membranes investigated; such depletion may lead to lack of vitamin D, an unwanted condition in HD patients 25 that may have a negative impact on survival.…”
Section: Introductionmentioning
confidence: 99%